Qiushi Academy (Adv. Mater. 14/2017). Issue 14 (April 2017) - Unknown
Abstract : Qiushi Academy, the predecessor of Zhejiang University, was founded in 1897 and was one of the earliest modern academies (universities) of higher learning established in China. In its 120‐year history, the faculties and students of Zhejiang University have always been committed to cultivating talent with excellence, advancing science and technology, serving for social development, and promoting culture. Now Zhejiang University is one of the top comprehensive research universities in China.